Strategi Personal Branding Grup Musik di Media Sosial Instagram - Bagus Cahya Putra, Rizky; Rusdi, Farid (Fakultas Ilmu Komunikasi Universitas Tarumanagara, 2024)
Nallar is a music group that has just developed in Indonesia which consists of three (3) personnel, bringing the genre of Pop, rhythm & blues (R&B). This research discusses how Nallar uses personal branding by utilizing the social media Instagram, as support for Nallar in his work in the music industry in order to introduce the Nallar music group to the general public. This research uses personal branding theory with several existing aspects proposed by Peter Montoya, as a basis for making this research. The research that the researchers studied also used descriptive qualitative research methods, and the results of the research were personal branding of the Nallar music group using eight (8) aspects of Peter Montoya in supporting its activities, namely specialization, leadership, personality, differences, visibility, unity, determination. , and a good name. The importance of this research is that it is used as a reference for musicians or outside musicians in carrying out their personal branding activities. Then the conclusion of this research is that Nallar carries out his personal branding activities by creating interesting content by utilizing the features found on Instagram by using several aspects mentioned above to attract audiences or Instagram users as well as to become an example of music groups in Indonesia in work, with the aim of the Nallar music group being better known for the work they create. Nallar merupakan grup musik yang baru berkembang di Indonesia terdiri dari tiga (3) personil, dengan membawa aliran Pop, rhythm & blues (R&B). Penelitian ini mengangkat tentang bagaimana Nallar menggunakan personal branding dengan memanfaatkan media sosial Instagram, sebagai penunjang Nallar dalam berkarya di industri musik guna memperkenalkan grup musik Nallar pada khalayak ramai. Penelitian ini menggunakan konsep teori personal branding dengan beberapa aspek yang ada yang diusung Peter Montoya, sebagai landasan dalam pembuatan penelitian ini. Penelitian ini juga menggunakan metode penelitian kualitatif deskriptif, dan memiliki hasil penelitian yaitu pada melakukan personal branding grup musik Nallar menggunakan delapan (8) aspek dari Peter Montoya dalam menunjang kegiatannya, yaitu spesialisasi, kepemimpinan, kepribadian, perbedaan, terlihat, kesatuan, keteguhan, dan nama baik. Dari hasil penelitian ini didapat bahwa Nallar melakukan kegiatan personal branding dengan membuat konten-konten menarik dengan memanfaatkan fitur-fitur yang terdapat pada Instagram dengan menggunakan beberapa aspek yang tersebut diatas untuk menarik audience atau pengguna Instagram juga untuk menjadi contoh grup musik di Indonesia dalam berkarya, dengan tujuan grup musik Nallar bisa lebih dikenal dengan karya yang dibuatnya.